Influence of millimeter electromagnetic waves on the functional capabilities of the lower limb muscles in athletes - volleyball players - Nasibullin, G.; Bobro, E.; Gushcha, S.; Badiuk, N. (Journal of Education, Health and Sport, 2021)
The authors, when observing 22 athletes - volleyball players of different volleyball specialization, assessed the effect of millimeter electromagnetic waves (EMW) on the functional state of the muscular system of the lower extremities. The electromagnetic effect was carried out using the "Complex SP 80" apparatus (frequencies 3900 - 4120 kHz were used). Electrodes were applied to the muscles of the thigh and lower leg, sinusoidal discharges were applied for 10 seconds during the strength training period. The results of observations showed that under the influence of EME, the height of the jump increases by 7%, due to the increase in the energy of the jump and its intensity. The release of the activity of the knee joint is also noted. The authors believe that under the influence of EME, the transmission of regulatory impulses in neuromuscular contact improves, which contributes to the synchronization and strength of contractions of the muscle fiber bundles. Also, under the influence of EMW, blood microcirculation in the muscle improves.